2018
DOI: 10.1186/s41182-018-0114-9
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis disease burden and attributable risk factors in Nigeria, 1990–2016

Abstract: BackgroundAccording to the World Health Organization, Nigeria is one of the countries with a high burden of tuberculosis (TB) worldwide. Improving the burden of TB among HIV-negative people would require comprehensive and up-to-date data to inform targeted policy actions in Nigeria. The study aimed to describe the incidence, prevalence, mortality, disability-adjusted life years (DALYs) and risk factors of tuberculosis in Nigeria between 1990 and 2016.MethodsThis study used the most recent data from the global … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
46
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 47 publications
(64 reference statements)
1
46
1
Order By: Relevance
“…Similarities in Chinese and Korean trends in TB burden might be due to the relatively low incidence of HIV-positive TB in both countries compared with many countries with a high HIV prevalence, with 1.2 cases per 100,000 in China and 0.63 per 100,000 population in Korea [ 29 ]. In contrast to our findings, in Nigeria, the TB burden among HIV-negative individuals was the highest in those aged 15–49 years [ 32 ]. According to the GBD studies, DALYs due to the drug-susceptible TB among HIV/AIDS positives were the highest in males aged 30–39 globally [ 9 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Similarities in Chinese and Korean trends in TB burden might be due to the relatively low incidence of HIV-positive TB in both countries compared with many countries with a high HIV prevalence, with 1.2 cases per 100,000 in China and 0.63 per 100,000 population in Korea [ 29 ]. In contrast to our findings, in Nigeria, the TB burden among HIV-negative individuals was the highest in those aged 15–49 years [ 32 ]. According to the GBD studies, DALYs due to the drug-susceptible TB among HIV/AIDS positives were the highest in males aged 30–39 globally [ 9 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies have estimated the annual percentage change of the age-standardized incidence rate when investigating global trends in the incidence of TB. [19][20][21][22][23] While this metric is a good indicator, it was not applicable to the present study for several reasons: (1) the annual percentage change represents the degree of change compared with the previous year, while the incidence in the 2020 milestone of the WHO End Tuberculosis Strategy is compared with 2015; (2) an annual percentage change estimated using a long period of data (eg, 10+ years) does not represent the trend after 2015; and (3) the 2020 milestone of the WHO End Tuberculosis Strategy is to reduce the incidence rate of TB by 20%, and not the agestandardized incidence rate. We, therefore, chose the annual percentage change in the incidence rate of TB based on 2015 to evaluate the trend of TB incidence rate after 2015 in addressing the purpose of this study.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, it replicates in the report of Cadmus et al, (2018) where Nigeria is rated fourth among the countries with the highest burden of TB. Similarly, Ogbo et al, (2018) reported prevalence trends of TB in Nigeria to be 158 in 100,000 people, and the total number of TB attributable deaths was 39,933 in 2016.…”
Section: Environmental and Socio-economic Factors As Tuberculosis Drimentioning
confidence: 96%
“…The prevalence of tuberculosis in Nigeria is shown in figure 2. The prevalence trends of TB in Nigeria were 158 in 100,000 people, and the total number of TB attributable deaths was 39,933 in 2016 (Ogbo et al, 2018). This study further shows decreases in prevalence and death cases from 2000 to 2016 in the country, but disease resurgence is also shown in figure 2.…”
Section: Environmental and Socio-economic Factors As Tuberculosis Drimentioning
confidence: 99%
See 1 more Smart Citation